Influence of local ionization on ionospheric densities in Titan’s upper atmosphere - Sagnieres,LBM; Galand,MIF; Cui,J; Lavvas,P; Vigren,E; Vuitton,V; Yelle,R; Wellbrock,A; Coates,A (Journal of Geophysical Research: Space Physics, 2015)
Titan has the most chemically complex ionosphere of the Solar System. The main sources of ions on the dayside are ionization by EUV solar radiation and on the nightside include ionization by precipitated electrons from Saturn's magnetosphere and transport of ions from the dayside, but many questions remain open. How well do models predict local ionization rates? How strongly do the ionization processes drive the ionospheric densities locally? To address these questions, we have carried out an analysis of ion densities from the Ion and Neutral Mass Spectrometer (INMS) from 16 close flybys of Titan's upper atmosphere. Using a simple chemical model applied to the INMS dataset, we have calculated the ion production rates and local ionization frequencies associated with primary ions inline image and inline image. We find that on the dayside the solar energy deposition model overestimates the INMS-derived inline image production rates by a factor of 2. On the nightside, however, the model driven by suprathermal electron intensities from the Cassini Plasma Spectrometer (CAPS) Electron Spectrometer (ELS) sometimes agrees, other times underestimates the INMS-derived inline image production rates by a factor of up to 2-3. We find that below 1200 km, all ion number densities correlate with the local ionization frequency, although the correlation is significantly stronger for short-lived ions than long-lived ions. Furthermore, we find that for a given N2 local ionization frequency inline image has higher densities on the day-side than on the nightside. We explain that this is due to inline image being more efficiently ionized by solar photons than by magnetospheric electrons for a given amount of N2 ionization.